Transformasi dari Hafalan ke Pemahaman Nilai-Nilai Qur'ani: Strategi Pembelajaran Bermakna Berbasis Deep Learning - Rizki Maulana; Nabilah Nurjannah; Aura Nurjannah; Muhammad Chepy Revy Revy; Abdul Fadhil (Advances In Education Journal, 2025)
Qur’anic learning in many educational institutions remains dominated by memorization-oriented approaches, enabling students to master the textual form of verses but not necessarily understand their moral meanings and embedded values. This study aims to describe the characteristics of memorization-based learning, analyze deep learning–based meaningful learning strategies for strengthening Qur’anic values, and assess their impact on students’ understanding and value internalization. Using a qualitative approach with a descriptive-analytical method, this research employs library study supported by a systematic literature review (SLR) as well as content analysis of books, journal articles, curricula, and learning materials related to meaningful learning theory and Qur’anic value education. The findings indicate that memorization-based learning tends to be textual, mechanical, and limited in fostering reflective understanding. In contrast, deep learning strategies— including tadabbur, Qur’anic project-based learning, case studies, collaborative learning, reflective journals, and experiential learning— effectively transform memorization into value comprehension through analysis, reflection, and contextual application. These findings underscore the need for an integrative Qur’anic learning design that harmonizes memorization, understanding, and value internalization to strengthen the orientation of meaningful Qur’anic education.